2014
DOI: 10.1074/jbc.m113.529354
|View full text |Cite|
|
Sign up to set email alerts
|

Mediator, TATA-binding Protein, and RNA Polymerase II Contribute to Low Histone Occupancy at Active Gene Promoters in Yeast

Abstract: Background:Promoters of active genes in eukaryotes are typically depleted of histone proteins. Results: Histone eviction from the induced CHA1 promoter is compromised by mutations in transcription factors, and higher histone occupancy is also seen at constitutively active promoters in such mutants. Conclusion: Preinitiation complex formation promotes reduced histone occupancy at active gene promoters. Significance: Preinitiation complex components participate in chromatin remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
(121 reference statements)
1
21
0
Order By: Relevance
“…This idea is supported by studies of S. cerevisiae showing the occupancy of the SAGA coactivator complex at certain promoters can be interdependent with (14) or dependent on (13) Mediator and its tail module subunits. A recent study shows that Swi/Snf activity at the S. cerevisiae CHA1 promoter also is dependent on Mediator tail module subunits (45). Consistent with such a scenario, we have found that the TADs of ScMed2 and ScMed3 appear to function redundantly in the induction of high levels of activated transcription.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This idea is supported by studies of S. cerevisiae showing the occupancy of the SAGA coactivator complex at certain promoters can be interdependent with (14) or dependent on (13) Mediator and its tail module subunits. A recent study shows that Swi/Snf activity at the S. cerevisiae CHA1 promoter also is dependent on Mediator tail module subunits (45). Consistent with such a scenario, we have found that the TADs of ScMed2 and ScMed3 appear to function redundantly in the induction of high levels of activated transcription.…”
Section: Resultssupporting
confidence: 72%
“…The S. cerevisiae Mediator tail module largely regulates SAGA-dependent genes and helps direct the activity of the SAGA and Swi/Snf coactivator complexes to specific promoters (13,14,45,47). The interaction of Mediator-associated activation domains with wellcharacterized targets of certain DNA-bound transcriptional activators (1), such as Tra1 (48), could explain how Mediator coordinates the recruitment of SAGA or other coactivators.…”
Section: Discussionmentioning
confidence: 99%
“…This double mutant was previously shown to lead to a loss of Tail module functions (Ansari et al, 2012, 2014; Paul et al, 2015; Zhang et al, 2004), so we will refer to these cells (med3Δ/med15Δ) as TailΔ. Very strikingly, Mediator occupancy at UAS regions was reduced to background level in TailΔ cells (Figures 3A and 3B, KIN28 WT).…”
Section: Resultsmentioning
confidence: 93%
“…The absence of prominent upstream Mediator peaks at most TFIID-regulated, tail module-independent promoters, in spite of the presence of Mediator at proximal promoter regions of these genes (10,11,17), underscores the possibility that Mediator is recruited to such targets by a distinct mechanism from that used at SAGA-regulated, tail module-dependent genes (38). Mediator can evidently be recruited in part via interactions with the general transcription machinery (39,40); such a mechanism could be consistent with patterns of Mediator occupancy that we observe here at TFIID-regulated, tail moduleindependent genes ( Fig. 3; Mediator has been reported to be associated with transcribed ORFs in both S. cerevisiae and S. pombe (7,9).…”
Section: Discussionmentioning
confidence: 99%